Depression, anxiety and perceived stress in women with and without PCOS: a community-based study. Issue 9 (22nd August 2018) - Damone, Anna L.; Joham, Anju E.; Loxton, Deborah; Earnest, Arul; Teede, Helena J.; Moran, Lisa J.
Abstract: Background: Polycystic ovary syndrome (PCOS) is associated with increased psychological distress in clinical populations. We aimed to assess depression, anxiety and perceived stress in women with and without PCOS in a large community-based sample and investigate the role of stress in contributing to and mediating the relationship between PCOS, depression and anxiety. Methods: A cross-sectional analysis was performed from the Australian Longitudinal Study of Women's Health (ALWSH) comparing women with ( n = 478) or without ( n = 8134) a self-reported diagnosis of PCOS. Main outcome measures were depression, anxiety and perceived stress measured using validated scales. The χ 2 and t tests were used to assess differences between groups. Univariable and multivariable regression were performed to determine factors contributing to each outcome. Results: Women reporting PCOS, compared with women not reporting PCOS, reported higher prevalence of depression (27.3% v. 18.8%), anxiety symptoms (50% v. 39.2%) and greater score for perceived stress (1.01 ± 0.03 v. 0.88 ± 0.01). After adjusting for body mass index, infertility and socio-demographic factors, women with PCOS were still more likely to be depressed, anxious and to have a higher level of perceived stress. There was a high-level mediation effect of stress between PCOS and both depression and anxiety. Conclusion: Compared with women not reporting PCOS, women reporting PCOS have increased depression, anxiety and perceived stress. Stress may play a role in the association between PCOS, depression and anxiety. Further studies should consider assessment and management of stress in PCOS as it may be relevant for understanding the aetiology and treatment of psychological distress.